Linear-range Extension for Linear Variable Differential Transformer Using Binomial Series - Wandee Petchmaneelumka; Kanoknuch Songsuwankit; Jakkapun Tongcharoen; Vanchai Riewruja (My University, 2020)
The linear-range extension technique for a linear variable differential transformer (LVDT) is described in this paper.Generally, the LVDT has a narrow linear operating range caused by its nonlinear transfer characteristic.To extend the linear operating range, the nonlinear behavior of the LVDT must be adjusted.In this paper, the circuit building block providing the LVDT inverse transfer characteristic using binomial series approximation is proposed for linearizing the nonlinear behavior of the LVDT.The third-order inverse transfer characteristic of the LVDT is synthesized from analog multipliers and a difference amplifier comprising an operational amplifier (opamp).All active devices used in this study are commercially available.Therefore, the attraction of the proposed technique is in the simple configuration and low cost, making it suitable for an embedded measurement system.The performance of the proposed technique is discussed in detail.Simulation and experimental results confirming the performance are also included.As a result, the linear range of the commercial LVDT used in this study can be extended more than 500%.The full scale error of the measured value is about 0.23% over the entire operating range.
Keywords: Linear range; Digital Filter Design and Implementation